Fatwa-Fatwa Falakiyah Majelis Ulama Indonesia: Peran Majelis Ulama Indonesia dalam Perkembangan Diskursus Falakiyah Kontemporer di Indonesia - Rasyid, Muhammad; Izzuddin, Ahmad; Aseri, Muhsin (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This article aims to provide an in-depth examination of the role of the Indonesian Council of Ulama (Majelis Ulama Indonesia, MUI) in shaping, influencing, and directing the discourse of contemporary Islamic astronomy (‘Ilm al-Falak) in Indonesia through its fatwa-based decisions on falak-related issues. The main issue addressed in this study concerns how MUI, as a religious authority in Indonesia, serves to bridge the gap between scientific developments, divergent perspectives and methodologies among Muslims, and the community’s demand for uniformity in religious practices—particularly regarding the determination of the beginning of lunar months, prayer times, and the direction of the qibla. Practically, this issue is significant for understanding the relationship between religious authority, scientific advancement, and societal needs. The research employs a normative legal method, adopting uṣūl al-fiqh, astronomical, and socio-political approaches. The data sources consist of seven MUI fatwas on falak-related matters, encompassing themes such as the determination of lunar months, qibla direction, and prayer times. The data were analyzed using content analysis. The findings of this study highlight three significant roles of MUI in the discourse of contemporary Islamic astronomy in Indonesia: (1) formulating and establishing guidelines on falak-related issues; (2) acting as the primary mediator in resolving methodological and interpretative differences among Indonesian Muslims regarding falak matters; and (3) integrating religious understanding with scientific perspectives in the field of ‘Ilm al-Falak. Consequently, MUI’s role is crucial in maintaining coherence and legal certainty in Islamic law concerning falak in Indonesia, although there remains room for more intensive collaboration with academic scholars and modern astronomers to achieve broader consensus.